Actor-Network and Translation in Engineering Laboratory: A Case Study of Universitas Indonesia Civil Engineering Testing Laboratory - Sargani, Fazar Ramdhana (Masyarakat: Jurnal Sosiologi, 2019)
Actor-Network Theory (ANT) has been implemented to study various topics in Indonesian contexts such as microcredit, coral reef, contestation within the sustainable energy project, and civil-military relations. However, ANT is seldom used to examine laboratories as working assemblages in Indonesia, despite its crucial role in producing technological knowledge. In order to fill that research gap, this article intends to illustrate ANT implementation in studying the work of a laboratory, specifically at the Materials and Structure Lab and Civil Engineering Testing Lab of Universitas Indonesia using the concept or process of translation. This study found that a laboratory consists not only of human actors, such as authoritative experts, but alsoof non-human actors—e.g. buildings and equipment or machines. During its performance, the laboratory establishes an association, which is not only by creating, but also cutting off or choosing relations in accordance with the needs of the network, without all the actors being fully aware of it. This shows ANT’s limit in investigating elements outside the actions of actors in creating a network. The qualitative methodological approach is utilized with the consideration of better meeting the principles of ANT in following or tracing actors.